THE RELATIONSHIP BETWEEN GLYCEMIC VARIABILITY AND GLYCEMIC LOAD/GLYCEMIC INDEX IN PATIENTS WITH TYPE 2 DIABETES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The International Diabetes Federation has recognized the importance of regulating prandial glucose and the need to mitigate acute postprandial plasma glucose spikes, making it essential to target postprandial hyperglycemia. However, long-term dietary adherence remains both a crucial and challenging task. Therefore, developing a patient-oriented diet that takes into account individual preferences and is based on a traditional national diet, with the substitution of high-GI foods, can enable better control of glycemic variability.